Initiative and Implementation of The Public Service Innovation by Regional Government in Indonesia - Wisber Wiryanto (Jurnal Pemerintahan dan Politik Lokal, 2020)
Based on the Government Regulation No. 38/2017 Concerning Regional Innovation, the government of Indonesia has established an innovation policy for the regional government to improve public services. Therefore, it is the need a study to answer the question, how steps are needed by regional government agencies to carry out initiative and implementation of public service innovation? The purpose of this study, to find out about steps, problems, and solutions for regional government agencies in implementing public service innovation. The research method through the library research method uses a qualitative descriptive method. Data collection techniques using printed and electronic media instruments, websites to collect secondary data which is relevant for this study. Furthermore, a qualitative analysis technique was used to analyze data. The locus of this study was selected through a purposive sampling technique, so the regional government agencies with implemented public service innovation can be selected. This study was conducted in 2019. The results of this study shown, there are variations among regional government agencies in implementing public service innovation. On the one hand, some regional government agencies have implemented both initiative and implementation of public service innovation. While on the other hand, some regional government agencies have not yet implemented initiatives and implementation of public service innovation. Therefore, some regional government agencies need to be made as an innovation laboratory to encourage public service innovation.